INFLUENCE OF IRRIGATION REGIMES AND NITROGEN LEVELS ON GROWTH AND YIELD OF RICE UNDER MECHANISED SRI CULTIVATION - G . VIJAYSHEKAR; M. MALLA REDDY; R . MAHENDER KUMAR (The Bioscan, 2021)
A field experiment was carried out during kharif 2014 on clay loam soil at Indian Institute of Rice Research, Hyderabad with an objective to study the response of rice to irrigation regimes and nitrogen levels under MSRI (Mechanised System of Rice Intensification) cultivation. The experiment was laid out in a split plot design with three replications. Three irrigation regimes were taken as main plots and four nitrogen levels in subplots. Results revealed that taller plants, high LAI, higher tiller and dry matter production were observed with the maintenance of saturation up to panicle initiation (PI) stage. Irrigation to maintain saturation level up to PI stage had registered significantly higher grain yield (7386 kg ha -1 ), which was 7.9 and 5.6 % higher than submergence throughout the CGP (6804 kg ha -1 ) and AWDI (6979 kg ha -1 ), respectively. Significantly higher values of growth parameters were recorded with 180 kg N ha -1 . Significantly higher grain yield (8366 kg ha -1 ) was reported with180 kg N ha -1 but the difference between 180 and 150 kg N ha -1 is very narrow (5.9 %) compared to lower levels, which were 20.2 and 36.5 % lower than the 180 kg N ha -1